2017
DOI: 10.31219/osf.io/z264e
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Undergraduate Learning Assistants to Aid in Course Redesign

Abstract: Research has identified potential difficulties for students enrolled in large classes. Large classes reduce opportunities for faculty-student interaction, which may predict decreased learning, retention rates, and student performance. It is therefore important to increase opportunities for faculty-student interaction. One successful tactic for increasing this interaction in large classes involves the utilization of undergraduate peers as class assistants. This manuscript describes the implementation of Undergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Previous studies have shown that instructional team–student interactions play a vital role in a college students’ persistence in engineering, their engagement with the course content, and their academic success. 9,30,31 The results of this study align with this previous research, as the Statics students who engaged with the LAs, specifically the two students that were interviewed, placed a significant value and importance on those increased interactions in the class and tutoring out-of-class. In addition to increasing interactions within the course, the LAs continued to support student learning through individualized learning experiences.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have shown that instructional team–student interactions play a vital role in a college students’ persistence in engineering, their engagement with the course content, and their academic success. 9,30,31 The results of this study align with this previous research, as the Statics students who engaged with the LAs, specifically the two students that were interviewed, placed a significant value and importance on those increased interactions in the class and tutoring out-of-class. In addition to increasing interactions within the course, the LAs continued to support student learning through individualized learning experiences.…”
Section: Discussionsupporting
confidence: 85%
“…7 Limited instructional team-student interactions have been shown to promote passive learning, which has been shown to be one of the least effective learning methods for students. [8][9][10][11][12][13] Alternatively, in multiple studies, high amounts of instructional team-student interactions have been shown to positively impact student engagement and the overall student experience with the course and its content. 9,13 In the case of LAs, LAs are undergraduate students who, as members of the instructional team, support their peers' learning, form and facilitate classroom discussion, and encourage active engagement with the course and its content.…”
Section: Background and Motivationmentioning
confidence: 99%
“…We note, however, that systemic changes to course instruction may cause an initial decrease in student achievement before seeing improvement [12], and this study is an impetus for further studies that identify factors that may be different in Calculus 2 instruction.…”
Section: Resultsmentioning
confidence: 74%
“…Implementation of an undergraduate Learning Assistant program is one strategy to increase engagement with students as it has been found to be effective in promoting student learning, engagement and satisfaction, as well as improving student retention (Groccia & Miller, 1996;Jardine et al, 2020;Knight et al, 2015;Pivkina, 2016;Talbot et al, 2015). In addition, studies have shown that incorporating LAs not only improves student performance but also supports course redesign efforts by faculty (Jardine et al, 2020;McHenry et al, 2010;Pavlacic & Buchanan, 2017). LAs, who recently have taken the course, provide faculty with feedback from a student's perspective on their course redesign, which has been shown to increase faculty satisfaction with their courses.…”
Section: Discussionmentioning
confidence: 99%